Asuhan Kebidanan Pada Ny. A dengan Partus Prematurus di Puskesmas Ngesrep Semarang Tahun 2024 - Delvitayani Delvitayani (An-Najat, 2025)
Pregnancy and childbirth are important physiological processes in a woman's life, but preterm labor can occur before 37 weeks of gestation, increasing the risks for mother and baby. In Indonesia, the prevalence of preterm labor is estimated at 10.2%, with risk factors such as maternal age, pregnancy history, infections and socio-economic conditions. This case poses a big challenge in maternal and child health services, because it can cause serious complications for premature babies, such as problems with breathing, growth and neurological development. This study aims to analyze midwifery care for Mrs. With premature labor at the Ngesrep Community Health Center, Semarang. The method used is descriptive research with a case study approach, where primary data is obtained through interviews, observation and medical record documentation. The research results show that even though the mother is in a stable physical condition, the mother's anxiety regarding the condition of the premature baby needs serious attention. The interventions carried out include psychological counseling for mothers and intensive care for premature babies. It is hoped that this research will provide useful insight in improving the quality of maternal and child health services, especially in dealing with premature births.